Toxigenic fungi isolated from dried vine fruits in Argentina - Romero, Stella Maris (2005)
To evaluate the potential for mycotoxin production by fungi in dried vine fruits, the mycobiota was determined both before and after surface disinfection. Predominant genera were Aspergillus (50.2%), Eurotium (21.4%) and Penicillium (13.5%). Aspergillus section Nigri (“black aspergilli”) were isolated with relatively high frequency. Aspergillus niger was the most common species but only 3 of 293 isolates screened were ochratoxin A (OTA) producers. Aspergillus carbonarius was less common but 96% of 48 strains screened were ochratoxigenic. OTA was not produced by A. japonicus. Other toxigenic fungi detected were A. ochraceus (3 strains produced OTA), Aspergillus flavus (5 strains produced cyclopiazonic acid but not aflatoxins), P. citrinum (19 strains were strong citrinin producers) and Alternaria alternata (15 strains were producers of tenuazonic acid, alternariol and alternariol methyl ether). In spite of the high incidence of A. carbonarius capable of producing OTA, low levels of this toxin were detected in the samples analysed.